Complete mitochondrial genome and phylogenetic analysis of the Gray’s pipefish Halicampus grayi Kaup 1856 - Jianzhen Chen; Mengru Lai; Siya Sun; Guangji Zhang; Yuqing Ge; Rubin Cheng (Mitochondrial DNA. Part B. Resources, 2019)
In the present study, the complete mitochondrial genome of H. grayi was determined and annotated. The circular mitogenome is 16,959 bp in length and contains 13 protein-coding genes (PCGs), two rRNA genes, 22 tRNA genes, and a control region. Most of the PCGs start with ATG, but CO1 begins with a GTG start codon. Phylogenetic analysis revealed that H. grayi was strictly related to network pipefish Corythoichthys flavofasciatus with 100% bootstrap support value. This work provides basic molecular information that would be useful for further investigation on conservation genetics and evolutionary relationships of H. grayi.